Physical and chemical characterization of theobroma caca l. pulp produced in the mesorregiao do Jaguaribe, Ceará, Brazil (Research, Society and Development, 2020)
The adaptation of cacao and the quality of its fruits produced in the Northeast, mainly in the Jaguaribe Valley - Ceara, is still under study. Therefore, the objective was to characterize the quality of fruits of six cocoa genotypes produced in the Mesoregion of Jaguaribe, Northeast Brazil. Orchards of six genotypes of Theobrama cacao (PS1319, CCN51, CEPEC 2002, CEPEC 2004, CEPEC 2005 and CEPEC 2006) were implanted in the city of Russas, Ceará, Brazil. In the fruit and vegetable processing laboratory, the fruits were dimensioned in terms of shape and pulped to determine the characteristics of pulp yield, pH, titratable acidity, soluble solids, ascorbic acid, chemical composition and bioactive compounds. According to the results obtained, the ‘PS1319’ genotype has higher pulp percentages, high levels of ascorbic acid, moisture and proteins, and can be considered the best genotype. However, if the goal is to produce the crop for the use of seeds in the chocolate industry, the ‘CCN51’ genotype showed better characteristics such as fresh weight and larger seed diameters, compared to the other genotypes. Therefore, the genotypes ‘PS1319’ and ‘CCN51’ are the most suitable when it is desired to use them in the production of food products such as chocolate.